The Incidence Of Tori In Malaysians- A Retrospective Analysis - Shareif Alani, Mohammed Subhi (IIUM Medical Journal Malaysia, 2017)
Introduction: The aim of this study was to determine the incidence of torus palatinus and torus mandibularis in Malaysians. The objectives are to evaluate the incidence of tori according to ethnicity, to assess the incidence of tori according to gender and to determine the incidence of torus palatinus vs torus mandibularis. Materials and Methods: This study was carried out in MAHSA Dental Clinic by collecting the data of 97 patients (15-74 years old) with 133 torus palatinus and torus mandibularis (2008-2014). Data included patient’s age, race, gender, presence of the tori with their size; number and location. The presence of tori was confirmed by clinical inspection. Subjects were classified by their ethnicity as well as location of the tori. Impression and study casts were made for assessment of the size and shape of the tori. The tori were measured by A digital caliper and average size was graded by Reichart’s classification. The data analyzed by Chi-Square test Results: Out of the 133 cases; 40% were Malay, 37% were Chinese and 23% were Indians with no significant finding (p-value=0.2783). 47.4% of the subjects were from the third decade of life. Male to female ratio 1:2 with 37% male and 63% female. Among all the cases, 53% were torus palatinus, 19% were torus mandibularis and 28% had both. Larger size of tori was found in Malays. Conclusion(s): The frequency of tori is relatively high in Malaysian population but unrelated to ethnicity. The etiology of tori seems to be multifactorial in nature and needs more researches to unravel.